Aspects of rural landscape planning related to abandoned places and objects - Markova, Madara (Landscape Architecture and Art, 2021)
The study gives insight into the definition of abandoned places and objects in rural landscape planning. The goal of the study is to identify the essential aspects of rural landscape planning, that are related to abandoned places and objects, to use these findings from the literature review in further research already defining abandoned places and objects and giving guidelines for these kinds of places and object inclusion in planning documents. Rural landscape planning is considered to be the beginning of the development of planning, but planning issues have moved these days in the direction of metropolitan areas. There are still relevant initial planning goals in rural landscape planning - the creation of a quality living environment and job creation. Nowadays the importance of the landscape planning approach at the local level is emphasized. Rural landscape development and change processes are closely linked to the Common Agricultural Policy. Abandoned place/object in the context of planning can be considered as one that is not used for one year or more according to the defined function, or a place/object as abandoned, defined in human perception.